Faktor yang Memengaruhi Perilaku Seks Pranikah pada Remaja - Venansius Alfridus; Jacob Matheos Ratu; Pius Werawan; Luh Putu Ruliati; Imelda F. E. Manurung (Journal of Telenursing (JOTING), 2022)
This study aims to determine the factors that influence premarital sexual behavior in adolescents and the influence of these factors on adolescent behavior in Alok District and Bola District. The method used is quantitative with a cross-sectional approach to 104 adolescents determined proportionally by random sampling. Data analysis used a simple logistic regression test. The results showed that there was a significant relationship between knowledge (p = 0.021; OR = 3,286), religious level understanding (p = 0.020; OR = 6.718), family roles (p = 0.000; OR = 7,192), peers (p = 0.031; OR = 9.444) and sources of information (p = 0.030; OR = 9.874) on premarital sex behavior in adolescents, while cultural factors had no relationship (p = 0.069; OR = 0.468). In conclusion, there is an influence between knowledge, understanding of the level of religion, the role of family, peers and sources of information on premarital sex behavior in adolescents. Keywords: Determinants, Adolescents, Premarital Sex